Dual‐energy CT imaging of nasopharyngeal cancer cells using multifunctional gold nanoparticles. Issue 9 (13th November 2019) - Khademi, Sara; Sarkar, Saeed; Shakeri‐Zadeh, Ali; Attaran, Neda; Kharrazi, Sharmin; Solgi, Razieh; Reza Ay, Mohammad; Azimian, Hosein; Ghadiri, Hossein
Abstract : The purpose of this study is to measure the concentration of gold nanoparticles (AuNPs) attached to folic acid through cysteamin as the linker (FA‐Cys‐AuNPs) and AuNPs in KB human nasopharyngeal cancer cells using dual‐energy CT (DECT). In this study, nanoparticles with a size of ∼15 nm were synthesized and characterised using UV‐Vis, TEM, FTIR and ICP‐OES analyses. The non‐toxicity of nanoparticles was confirmed by MTT assay under various concentrations (40– 100 µg/ml) and incubation times (6, 12 and 24 h). To develop an algorithm for revealing different concentrations of AuNPs in cells, a corresponding physical phantom filled with 0.5 ml vials containing FA‐Cys‐AuNPs was used. The CT scan was performed at two energy levels (80 and 140 kVp). One feature of DECT is material decomposition, which allows separation and identification of different elements. The values obtained from the DECT algorithm were compared with values quantitatively measured by ICP‐OES. Cells were also incubated with AuNPs and FA‐Cys‐AuNPs at different concentrations and incubation times. Subsequently, by increasing the incubation time in the presence of FA‐Cys‐AuNPs, in comparison with AuNPs, DECT pixels were increased. Thus, FA‐Cys‐AuNPs could be a suitable candidate for targeted contrast agent in DECT molecular imaging of nasopharyngeal cancer cells.